Phenotype-genotype updates from familial Mediterranean fever database registry of Mansoura University Children’ Hospital, Mansoura, Egypt - Al-Haggar, Mohammad S. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Familial Mediterranean fever (FMF) is autosomal recessive disease that affects people from Mediterranean region, Europe and Japan. Its gene (Mediterranean fever [MEFV]) has more than 100 mostly non-sense mutations. OBJECTIVES: The objective of the following study is to provide some phenotype-genotype correlates in FMF by categorizing the Egyptian FMF cases from Delta governorates after analysis of the four most common mutations of MEFV gene (M680I, M694I, M694V, V726A). SUBJECTS AND METHODS: Clinically, suspected FMF cases using Tel-Hashomer criteria were enrolled in the study. Cases were referred to Mansoura University Children's Hospital that serves most of the most middle Delta governorates, in the period from 2006 to 2011. Subjects included 282 males and 144 females, mean age of onset 9.3 ± 2.2 years. All cases were analyzed for these mutations using amplification refractory mutation system based on the polymerase chain reaction technique. Five FMF patients agreed to undergo renal biopsy to check for development of amyloidosis. Analysis of data was carried out using SPSS (SPSS, Inc., Chicago, IL, USA). RESULTS: Mutation was found in 521 out of 852 studies alleles, the most frequent is M694V (35.4%) followed by M694I, V726A and M680I. 11 cases were homozygous; 7 M694V, 3 M680I and only one M694I case. Severe abdominal pain occurred in 31 (7.28%) but severe arthritis in 103 cases (24.2%). Strong association was found between arthritis and homozygous mutant compared with single and double heterozygous (72.7% vs. 33.3% and 20.24%, P < 0.001). Four amyloid cases were M694V positive. CONCLUSION: M694V allele is the most common among Egyptian FMF especially those with amyloidosis. We recommend routine check for amyloidosis in FMF cases to statistically validate this link.